High prevalence of circulating dual-class resistant Mycoplasma genitalium in asymptomatic MSM in Tokyo, Japan. Issue 2 (30th June 2021) - Ando, Naokatsu; Mizushima, Daisuke; Takano, Misao; Mitobe, Morika; Miyake, Hirofumi; Yokoyama, Keiko; Sadamasu, Kenji; Aoki, Takahiro; Watanabe, Koji; Uemura, Haruka; Yanagawa, Yasuaki; Gatanaga, Hiroyuki; et al.
Abstract: Objectives: To assess the prevalence and antibiotic resistance profile of Mycoplasma genitalium detected from urogenital/rectal swab samples obtained from MSM in Tokyo, Japan. Methods: We performed PCR-based screening for M. genitalium urogenital/rectal infection in 982 asymptomatic MSM between 1 January 2019 and 5 November 2020. Mutations in the antibiotic resistance-associated genes gyrA and parC and the 23S rRNA of M. genitalium were analysed. Results: The prevalence of M. genitalium infection was 6.1%: the prevalence of rectal and urogenital infection was 4.7% and 1.4%, respectively. Among the cases, 48 were successfully analysed for 23S rRNA, 41 for parC mutations and 37 for gyrA mutations. Macrolide- and quinolone-resistance associated mutations (23S rRNA and parC mutations) were observed in 43 (89.6%) and 28 (68.3%) cases, respectively. The quinolone-resistance associated mutation-harbouring variants also harboured macrolide-resistance associated mutations. The S83I mutation in the parC gene was most commonly identified (24 cases, 58.5%), and its combination with M95I or D99N mutation in the gyrA gene was observed in 9 of 36 successfully analysed cases (25.0%). No significant association was observed between the presence of antibiotic resistance and antibiotic exposure for either macrolides or fluoroquinolones ( P =  0.785 and 0.402, respectively). Conclusions: In Tokyo, there is an alarmingly high prevalence of M. genitalium harbouring macrolide and/or quinolone resistance-associated mutations in MSM, irrespective of antibiotic exposure. The high prevalence of M. genitalium strains with both parC and gyrA mutations limits the efficacy of sitafloxacin. Therefore, suitable alternatives are required to treat such M. genitalium infections.